Model-Based Software Regression Testing for Software Components - Gagandeep,; Kumar, Yogesh; Gupta, Jyotsna Sen (Gyan Management Journal, 2009)
This paper presents a novel approach of generating regression test cases from UML design diagrarr_· Regression testing can be systematically applied at the software components architecture level so as :: reduce the effort and cost of retesting modified systems. This approach consists of transforming a UJfj_ sequmce diagram of a component i11to a graphical structure called the control flow graph (CFG) and : ·· revised version into an Extended control flow graph (ECFG) The nodes of the two graphs are augmer.:1: with information necessary to compose test suites in terms of test case scenarios. This informatfor. · · collected from use case templates and class diagrams. The graphs are traversed in depth-first-order : : generate test scenarios. Further, the two are compared for change identification. Based on change informatfo.".. test cases are identified as reusable, obsolete or newly added. The regression test suite thus generated :.: suitable to detect any interaction and scenario faults.
Keywords: CFG; ECFG; Regression